Bustanul Arifin and A. Qodri Azizy on the Absorption of Islamic Law into National Law: a Discourse of Thinkin - Dwi Rahayu Sulistyaningrum (Pustaka Peradaban, 2022)
Bustanul Arifin and A. Qodri Azizy are two well-known Indonesian legal experts, especially in matters of Islamic law legislation in Indonesia. both of them have major contributions to the dynamics of Islamic law legislation in Indonesia. although both thoughts have been widely reviewed, most of them are still in separate partial reviews. Because of this, this paper seeks to present the thoughts of the two figures in one frame regarding the absorption of Islamic law into national law. The study was conducted using normative legal research methods, applying historical and conceptual approaches, and using qualitative analysis methods. The results of the study found that the two figures agreed on the urgency of absorbing Islamic law into Indonesian national law. Bustanul stated the importance of absorbing Islamic law through legislation. Meanwhile, A. Qodri Azizy put forward the eclecticism of Islamic law and general law. The development of post-reform democracy has made Islamic law able to compete with customary law, as well as Western heritage law in a democratic and free manner. So that all three of them can run eclectically without prioritizing Muslim majoritarianism